COMPARATIVE EVALUATION OF SURFACE ROUGHNESS OF FLOWABLE COMPOSITE RESIN AFTER BRUSHING SIMULATION WITH FLUORIDATED AND REMINERALISING TOOTHPASTE - AN IN VITRO STUDY (Cuestiones de Fisioterapia, 2023)
Introduction: Composite resin is the material of choice for anterior tooth restorations in adult and pediatric patients. Surface roughness is a crucial property in the success of dental restoration.Toothbrushing may influence the wear and surface roughness